2023
DOI: 10.3847/psj/acd538
|View full text |Cite
|
Sign up to set email alerts
|

Formation, Structure, and Detectability of the Geminids Meteoroid Stream

Abstract: The Geminids meteoroid stream produces one of the most intense meteor showers at Earth. It is an unusual stream in that its parent body is understood to be an asteroid, (3200) Phaethon, unlike most streams, which are formed via ongoing cometary activity. Until recently, our primary understanding of this stream came from Earth-based measurements of the Geminids meteor shower. However, the Parker Solar Probe (PSP) spacecraft has transited near the core of the stream close to its perihelion and provides a new pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Finally, Cukier & Szalay (2023) created a dynamical model of the Geminid meteoroid stream calibrated with Earth-based measurements and compared it to the observation of a dust environment near the Sun by the Parker Solar Probe (PSP). They found that the PSP data were more consistent with their model of a catastrophic formation scenario and least consistent with a cometary formation mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Cukier & Szalay (2023) created a dynamical model of the Geminid meteoroid stream calibrated with Earth-based measurements and compared it to the observation of a dust environment near the Sun by the Parker Solar Probe (PSP). They found that the PSP data were more consistent with their model of a catastrophic formation scenario and least consistent with a cometary formation mechanism.…”
Section: Introductionmentioning
confidence: 99%